Evaluation of the DC bus link capacitors and power transistor modules in the qualification testing of PV inverters. (15th October 2020) - Hacke, Peter; Clemens, Daniel; Thiagarajan, Ramanathan; Flicker, Jack; Igarashi, Hironobu
Abstract: To achieve useful, fair, and cost‐effective design qualification and type approval testing for PV inverters, two procedures were developed and demonstrated to evaluate the bus link capacitors and power transistor—and where applicable, its module—for long‐term reliability. We evaluate the inverter under simulated use conditions with heat run tests to find the highest operating temperatures reached by these components. The procedures are demonstrated in this study with a 4‐kVA class string inverter. The maximum temperature of the DC bus link capacitors was determined to be 76.4°C when the ambient temperature was at the inverter's maximum rated temperature of 60°C with derating occurring. On the other hand, the power transistor module's maximum temperature using the heat sink temperature as the index, 92.6°C, occurred in an ambient of 40.8°C when derating was not occurring. The conditions found for upper temperatures exhibited by these components are, respectively, proposed for implementation in the dry heat and thermal cycling tests in the IEC 62093 "Power conversion equipment for photovoltaic systems – Design qualification testing" international standard draft so that the levels applied in the tests are in proportion to those experienced in the field. As a result, fairer evaluation of inverter reliability is realized. Abstract : To achieve useful, fair, and cost‐effective design qualification and type approval testing for PV inverters, procedures were developed and demonstrated to evaluate the bus link capacitors and power transistor module. The conditions found for upper temperatures exhibited by these components are respictively implemented in the dry heat and thermal cycling tests in IEC 62093 "Power convertion equipment for photovoltaic systems – Desing qualifacation testing" draft so that the levels applied in the test are in proportion to those experienced in the field.